Case report: Combined therapy of bilateral subthalamic nucleus deep brain stimulation and spinal cord stimulation significantly improves motor function in a patient with multiple system atrophy with predominant parkinsonism - Li, Jiping; Mei, Shanshan; Zhang, Xiaohua; Wang, Yunpeng; Jia, Xiaofei; Liu, Jinlong; Xu, Erhe; Mao, Wei; Zhang, Yuqing (Frontiers in Neuroscience, 2022)
Multiple system atrophy with predominant parkinsonism (MSA-P) is a highly incapacitating disease with a short life expectancy and symptomatic therapy is still limited. In this report, we presented the case of a 65-year-old woman with a 3-year history of severe rigidity, bradykinesia, and gait dysfunction alongside severe freezing of gait diagnosed with MSA-P. She underwent combined therapy of bilateral subthalamic nucleus deep brain stimulation (DBS) and low-thoracic spinal cord stimulation (SCS). The double-blind evaluation of the Movement Disorder Society Sponsored Revision of the Unified Parkinson’s Disease Rating Scale part III and 7-m Timed Up and Go at follow-ups showed her cardinal parkinsonian symptoms benefit significantly from DBS stimulation, while the improvement of SCS was mainly embodied in lower-limb symptoms. The combined stimulation achieved a better improvement of motor function than either DBS or SCS stimulation alone. Most notably, the improvement of lower-limb symptoms was significantly enhanced by the combined stimulation.